LANDSCAPE AND OBJECT DETAILS IN VASYL STEFANYK’S NOVELLAS AND THEIR ENGLISH TRANSLATION - Karbashevska, Oksana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim of the article is an attempt of the literary analysis of personified landscape and object details in Vasyl Stefanyk’s novella “The Blue Book”, as well as of the translatological analysis of D. Husar-Struk’s rendering relevant text fragments into the English language. The tasks of the article: elaboration of reference, encyclopedic and scientific literature on the subject of the essence of such literary notions as the fictional detail, novella, landscape, object, falcon theory, personification; generalization of the Stefanyk literary studies as to the peculiarity of landscapes and objects of the short prose by the author of novellas; examination of translatological works concerning translation issues of V. Stefanyk’s novella texts into Germanic languages; singling out personified fictional details in the novella “The Blue Book” and establishment of their role; revelation of cases of D. Husar-Struk’s implementing translatological transformations during the translation of selected personified textual pieces; systematization and classification of these changes; definition of losses and gains in the English translated creation. The article employs complex research methods, namely general scientific research methods, such as analysis, synthesis and generalization, as well as a hermeneutic-interpretational (in the realm of interpreting fictional texts of the original and translation), linguistic, translatological, quantitative analysis. The practical significance. The materials and conclusions of the article may be used for writing students’ qualifying works, scientific works, developing and delivering lecture courses in the branch of literary and translation studies, in further scientific research of Vasyl Stefanyk’s creative work. The scientific novelty of the article is that for the first time in Ukrainian philology the personified landscape and object-detail things in V. Stefanyk’s novellas as well as their English translation became the subject of the complex analysis. As a result of the research the conclusions are drawn as to V. Stefanyk’s creative uniqueness to find its way in the landscape and object peculiarity of his novellas as well. For the author from Pokuttia ‒ a connoisseur of the human soul, the fictional detail performed a secondary, though integral and compensating function in his creative short prose works. The fictional language of the novellas in general, and particularly of the work “The Blue Book” (1897), witnesses that the personalization belongs to the writer’s favourite stylistic means of expression. In the named novella the personified plant world and objects, created by the human being, arise in Antin’s, i.e. the main hero’s one-side dialogue. Five fragments with personified fictional details in the novella “The Blue Book” are extracted. They perform such functions as filling with contents, psychologization of the situation and the character’s figure, and making them lyrical, as well as creating the plot, etc. In the translated creation “The Blue Book”, D. Husar-Struk preserved the novella’s ideas and matter, as well as the landscape-object space of the depicted events, conveyed the writer’s unique creative manner. The transition from the original to the translation was allowed due to the use of 38 transformations, as well as their 6 combinations. The mitigation of the aesthetic charge of the translated text took place in the process of recreating stylistic figures of inversion (4) and ellipsis (4), ethnically marked units (3), dialecticisms and the local tongue of Pokuttia (14), old-fashioned (2) and diminutive (1) words of the original.